Autophagy activity in cholangiocarcinoma is associated with anatomical localization of the tumor. - Gábor Lendvai (Public Library of Science (PLoS), 2021)
The presence of autophagy has been indicated in cholangiocarcinoma (CC), which disease has poor prognosis and limited treatment options. Recently, CC has been classified by anatomical localization as intrahepatic (iCC), perihilar (pCC) and distal (dCC), showing different clinical and molecular characteristics. Thus, our aim was to compare autophagy activity in CC samples resected from different anatomical locations. Further, we investigated whether autophagy could be modulated in cell lines originated from iCC and extrahepatic CC (eCC) following the treatments with autophagy inhibitory and inducing agents. Tissue microarrays were prepared from 70 CC (28 iCC, 19 pCC and 23 dCC), 31 adjacent non-tumorous and 9 hepatocellular carcinoma (HCC) samples. Autophagy markers LC3, p62 and Beclin1 as well as proliferation marker Ki-67 were monitored by immunohistochemistry and were associated with patients' survival. Modulation of autophagy was investigated in cell lines originated from iCC (HuH-28), eCC (TFK-1) and HCC (HepG2) by treating the cells with chloroquine (CQ) for inhibition and with Rapamycin, 5-Fluorouracil (5-FU) and Sorafenib for induction of autophagy. Our results indicated an inhibited autophagy in iCC and pCC tumor tissues, whereas active autophagy seemed to occur in dCC, especially in samples displaying low Ki-67 index. Additionally, low level of Beclin1 and high level of Ki-67 were associated with poor overall survival in dCC, suggesting the prognostic role of these proteins in dCC. Beside a baseline autophagy detected in each cell line, Rapamycin and 5-FU induced autophagy in iCC and HepG2 cell lines, Sorafenib in iCC cells. A chemotherapy agent in combination with CQ decreased IC50 effectively in the cell lines where basal and/or induced autophagy were present. In conclusion, we revealed differences in the autophagy activities of CC tissues and cell lines originated from different anatomical locations, which might influence patients' treatment. Our results also suggest a prognostic role of Beclin1 and Ki-67 in dCC.